Safeguarding Human and Environmental Rights Amidst Land-based Corporate Investments in Emerging Markets and How These Investments are Impacting Vulnerable Populations in Africa, Particularly Women - Gueldich , Hajer (Journal of Sustainable Development Law and Policy, 2025)
No Abstract.